Exact solutions of the ZK-MEWequation and the Davey-Stewartson equation - Zayed, E.M.E.; Filiz, Ali; Ekici, Mehmet; Sonmezoglu, Abdullah; Duran, Durgun (International Journal of Applied Mathematical Research, 2014)
In this paper we introduce a new version of the trial equation method for solving non-integrable partial differential equations in mathematical physics. Some exact solutions including soliton solutions, rational and elliptic function solutions to the generalized (2+1)-dimensional ZK-MEW equation and the generalized Davey-Stewartson equation with the complex coefficients are obtained by this method. Keywords: Extended trial equation method, generalized (2+1)-dimensional ZK-MEW equation, Davey-Stewartson equation, soliton solution, elliptic solutions.